A MAGYARORSZÁGI ENERGIATERMELŐ VÁLLALATOK MEGÚJULÓ ENERGIAFORRÁSOK ALKALMAZÁSÁVAL KAPCSOLATOS ÁLLÁSPONTJÁNAK VIZSGÁLATA - Haffner, Tamás (Közép-Európai Közlemények, 2019)
Energy policy has been an important strategic issue of nation-states after the 1950s. The unequal geographic location of fossil energy sources dominating power generation divided the world into energy importer and energy exporter countries. Hungary is an extremely poor state in terms of energy resources; the energy policy of the country and the structure of energy resources used have been and are determined by the energy import dependence. The ‘National Energy Strategy 2030’ developed on the basis of the guideline, adopted in 2011, specified insurance of long-term sustainability, security and economic competitiveness as primary objective of the Hungarian energy policy. The Government intends to guarantee security of supply, to enforce environmental considerations and depending on the options of the country, to stand up for solving global problems through implementation of the strategy. The strategy intends to achieve the termination of the electricity import balance of the country until 2030 by this ‘Nuclear-Coal-Green’ scenario based on these three pillars. Renewable energy sources can be used to generate electricity, heat energy and combined heat and power. Despite several technological and other barriers, use of renewable energy is constantly growing worldwide thus we can expect further expansion of renewable energy sources and the increase of their importance in energy supply. The positive attitude of the Hungarian energy producing company to creating new generation capacity using renewable energy sources is necessary to the increase the ratio of the renewable energy sources in the gross inland consumption in Hungary.